ADAMS model validation for an all terrain vehicle using test track data - Kanchwala, Husain; Chatterjee, Anindya (Sage, 2019)
MD ADAMS R is widely used for vehicle suspension modeling. In this paper we present modeling, simulation, and test track evaluation of an all terrain recreational vehicle. Our intention is to study the degree to which simplified ADAMS modeling actually matches human-driven vehicle response. For suspension model validation, a vehicle is generally tested on a four-post test rig and base-excitation is applied at four ground-wheel contacts. However, actual driving experience does not match idealized testing conditions. In this work the vehicle is manually driven on a variety of tracks at different speeds, and the vertical accelerations at four axle locations and four body points are measured. The same are then compared in detail against predictions from ADAMS simulation with vertical base excitation. The contribution of this paper is in identifying those aspects of the simulation results that match experiments well, and identifying possible sources for the observed mismatch, especially under more severe test conditions.
Keywords: ATV; ADAMS model; suspension; model validation; field testing